2017
DOI: 10.1007/s12072-017-9837-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous bacteremia and spontaneous bacterial peritonitis share similar prognosis in patients with cirrhosis: a cohort study

Abstract: Short-term acute kidney injury and mortality rates were similar in patients with spontaneous bacteremia and spontaneous bacterial peritonitis. Risk assessment of patients with spontaneous bacteremia can be performed with baseline MELD score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
10
0
5
Order By: Relevance
“…Survival after the first episode is estimated to be 40% at 1 year 14. Acute kidney injury occurs in as much as 54% of the patients, and acute-on-chronic liver failure occurs in 35%–60% of the patients, despite appropriate treatment 1518. In Table 1, the incidence of death and acute kidney injury in patients with spontaneous bacterial peritonitis is detailed.…”
Section: Clinical Aspects and Bacteriologymentioning
confidence: 99%
“…Survival after the first episode is estimated to be 40% at 1 year 14. Acute kidney injury occurs in as much as 54% of the patients, and acute-on-chronic liver failure occurs in 35%–60% of the patients, despite appropriate treatment 1518. In Table 1, the incidence of death and acute kidney injury in patients with spontaneous bacterial peritonitis is detailed.…”
Section: Clinical Aspects and Bacteriologymentioning
confidence: 99%
“…An earlier version of this work was presented as an abstract at the 27th Annual Conference of APASL (Asian Pacific Association for the Study of the Liver), March 14–18, 2018, New Delhi, India [ 50 ].…”
Section: Disclosurementioning
confidence: 99%
“…In the latter study, MDR infections accounted for 18%-23% of all identified bacteria[22]. Several authors have reported similar or even higher rates of MDR bacteria in different geographies and settings (up to one-half of bacterial infections in health-care acquired settings were caused by MDR bacteria)[23,24]. The main risk factors identified for the development of MDR infections were prior contact with the health-care system, a nosocomial or health-associated origin of infection, the use of norfloxacin prophylaxis, recent use of other antibiotics (cephalosporins or beta-lactams) or recent infection by MDR bacteria[22,23,25].…”
Section: Pitfalls Of Antibiotic Prophylaxis In Cirrhosis: Emergence Omentioning
confidence: 99%